2014
DOI: 10.11622/smedj.2014052
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and radiological characteristics of fabellae in an Asian population

Abstract: RESUlTSThe incidence of fabellae was 31.25% in our study cohort. The median length, thickness, width and distance of the fabella from the lateral femoral condyle were 7.06 mm, 4.89 mm, 6.12 mm and 33.19 mm, respectively. The fabella was consistently bony and located in the lateral head of the gastrocnemius, with 52% of the fabellae having an articulating facet. Fabellae in men were found to be larger than in women, although the difference was not statistically significant. The presence of an articulating groov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
47
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 11 publications
12
47
3
1
Order By: Relevance
“…Se ha encontrado en 22,8 % (bilateral en 15,2 % y unilateral en 7,6 %); Egerci et al); Iborra et al analizando 200 radiografías de individuos Españoles, lo localizó en 23% (bilateral en 85 %); Lencina en 2007 estudió un grupo de individuos Argentinos en 22 articulaciones de cadáveres y lo encontró en 18,2 % y en una serie radiológica de 214 pacientes (434 radiografías) visualizó su presencia en 20,73 %. Se ha encontrado también en mayor porcentaje, 31,25 % en un grupo Asiático (Chew et al, 2014), así como en 27,8 % en cadáveres de un grupo de individuos Sudafricanos (Phukubye & Oyedele). Los resultados obtenidos en nuestro estudio radiológico han mostrado valores más altos, 37,5% de los casos.…”
Section: Discussionunclassified
“…Se ha encontrado en 22,8 % (bilateral en 15,2 % y unilateral en 7,6 %); Egerci et al); Iborra et al analizando 200 radiografías de individuos Españoles, lo localizó en 23% (bilateral en 85 %); Lencina en 2007 estudió un grupo de individuos Argentinos en 22 articulaciones de cadáveres y lo encontró en 18,2 % y en una serie radiológica de 214 pacientes (434 radiografías) visualizó su presencia en 20,73 %. Se ha encontrado también en mayor porcentaje, 31,25 % en un grupo Asiático (Chew et al, 2014), así como en 27,8 % en cadáveres de un grupo de individuos Sudafricanos (Phukubye & Oyedele). Los resultados obtenidos en nuestro estudio radiológico han mostrado valores más altos, 37,5% de los casos.…”
Section: Discussionunclassified
“…On the other hand, Tabira et al [35] observed 46 out of 75 fabellae to be osseous and 24 cartilaginous in terms of their structure. In another study conducted in Far East, Chew et al [2] investigated the combination of MRI and radiography and established the prevalence of the fabella to be 31.25% and reported that all of these cases had an osseous structure (cartilaginous cases can be detected in MRI). This study originates from Singapore and identified the prevalence of the fabella to be lower than those specified in South-Eastern Asian studies.…”
Section: Discussionmentioning
confidence: 99%
“…Why did they show no contact? In adults, almost half of fabellae do not carry a facet for articulation to the lateral femoral condyle [3]. Thus, also in foetuses, there were likely to be two types of fabellae: 1) a real sesamoid facing the joint cavity and 2) a false sesamoid without facet.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and bony nature of fabellae in human adults has been found to vary, with studies showing incidence rates of 66.6% (44% bony) [8]; 23.5% (72% bony) [13]; 86.9% (56% bony) [24]; and 31% (100% bony) [3]. Almost half of fabellae carry a facet for articulation to the lateral femoral condyle [3]. A bony, but not an elastic-textured, fabella has been found to correlate with thickening of the fabellofibular ligament to strengthen the posterolateral corner of the knee [11].…”
Section: Introductionmentioning
confidence: 99%